Control of Oxidation State of Eu Ions in Na2O–Al2O3–SiO2 Glasses. Issue 4 (28th January 2016) - Nogami, Masayuki; Koiwai, Akihiko; Nonaka, Takamasa
Abstract : Glasses doped with well‐controlled Eu 3+ and Eu 2+ ions have attracted considerable interest due to the possibility of tuning the wavelength range of the emitted light from violet to red by using their 5 D0 → 7 Fj and 5 d –4 f electron transitions. Glasses were prepared to dope Eu 3+ ions in a Na2 O–Al2 O3 –SiO2 system, and the changes in the valence state of Eu 3+ ions and the glass structure surrounding the Eu atoms during heating under H2 atmosphere were investigated using fluorescence spectroscopy, X‐ray absorption fine‐structure spectroscopy, and 27 Al magic‐angle spinning solid‐state nuclear magnetic resonance spectroscopy. The reduction behavior of Eu 3+ ions was dependent on the Al/Na molar ratio of the glass. For Al/Na < 1, the Al 3+ ions formed the AlO4 network structure accompanied by the Na + ions as charge compensators; the Eu 3+ ions occupied the interstitial positions in the SiO4 network structure and were not reduced even under heating in H2 gas. On the other hand, in the glasses containing Al2 O3 with the Al/Na ratio exceeding unity, the Eu 3+ ions commenced to be coordinated by the AlO4 units in addition to the SiO4 network structure. When heated in H2 gas, H2 gas molecules reacted with the AlO4 units surrounding Eu 3+ ions to form AlO6 units terminated with OH bonds, and reduced Eu 3+ ions to Eu 2+ via the extracted electrons.